A simplified model of Type‐4 wind turbine for short‐circuit currents simulation analysis - Yuxi Wang; Minghao Wen; Yu Chen (IET Generation, Transmission & Distribution, 2022)
Abstract The electromagnetic transient (EMT) model of Type 4 wind turbine generator (WTG) requires a small simulation step, and cannot be simplified based on Thevenin‐Norton theorem, which results in the low simulation efficiency of large‐scale Type 4 WTG‐based wind power plants (WPPs) widely connected to the power grid, bringing challenges to the short‐circuit currents analysis in the research of protection. Therefore, in order to solve the problem of low simulation efficiency, a simplified model of Type 4 WTG is proposed based on the principle of internal active power balance of Type 4 WTG. The simplified model is represented by controlled voltage source, which eliminates the power electronic switch and DC‐link, greatly simplifies the typical EMT model of Type 4 WTG, and does not require small simulation step. The simplified model has simple modelling process and high universality of modelling method. The simulation results show that the proposed model can accurately reflect the EMT characteristics of Type 4 WTG under fault. Compared with the typical EMT model, the simulation time of this simplified model is significantly reduced, and the EMT simulation efficiency of the power grid connecting with large‐scale Type 4 WTG‐based WPPs has been effectively improved.